2016
DOI: 10.3847/2041-8205/830/1/l9
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Electron Thermal Conduction in the High Β Intracluster Medium of Galaxy Clusters

Abstract: Understanding the thermodynamic state of the hot intracluster medium (ICM) in a galaxy cluster requires a knowledge of the plasma transport processes, especially thermal conduction. The basic physics of thermal conduction in plasmas with ICM-like conditions has yet to be elucidated, however. We use particle-in-cell simulations and analytic models to explore the dynamics of an ICM-like plasma (with small gyroradius, large mean-free-path, and strongly sub-dominant magnetic pressure) induced by the diffusive heat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 23 publications
2
73
1
Order By: Relevance
“…The recent 1D PIC simulations by Roberg-Clark et al (2016) have also demonstrated that strictly parallel whistler waves are incapable of regulating the electron heat flux in a collisionless plasma. However, the initial electron VDF set by Roberg-Clark et al (2016) is an asymptotic solution of the collisional Fokker-Plank equation (e.g., Pistinner & Eichler 1998), that is very different from electron VDFs typical for the solar wind Maksimovic et al 1997;Tong et al 2019b). In contrast to Roberg-Clark et al (2016), we have presented 1D PIC simulations of the classical WHFI with initial electron VDFs more relevant for the solar wind, so that the results of the simulations can be compared to in-situ measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The recent 1D PIC simulations by Roberg-Clark et al (2016) have also demonstrated that strictly parallel whistler waves are incapable of regulating the electron heat flux in a collisionless plasma. However, the initial electron VDF set by Roberg-Clark et al (2016) is an asymptotic solution of the collisional Fokker-Plank equation (e.g., Pistinner & Eichler 1998), that is very different from electron VDFs typical for the solar wind Maksimovic et al 1997;Tong et al 2019b). In contrast to Roberg-Clark et al (2016), we have presented 1D PIC simulations of the classical WHFI with initial electron VDFs more relevant for the solar wind, so that the results of the simulations can be compared to in-situ measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Once thermal conduction takes place, the sharp temperature gradient will quickly smooth out and the rate will drop roughly as t 1/2 . (b) Heat flux might be significantly suppressed by magnetic field geometry and microscopic plasma instabilities in the cluster gas (Roberg-Clark et al 2016, 2018b. Although we include magnetic fields in the injection of the jets, the ICM is not magnetized in our simulations.…”
Section: The Conduction Rate and Energy Budgetmentioning
confidence: 99%
“…The observed radial evolution of the angular width of suprathermal field-aligned electron population (strahl electrons) in the solar wind (e.g., Hammond et al 1996;Graham et al 2017) requires pitch-angle scattering that can be potentially provided by whistler waves (Vocks et al 2005;Shevchenko & Galinsky 2010;Vocks 2012;Kajdič et al 2016;Vasko et al 2019). Whistler waves may also suppress the electron heat flux in collisionless or weakly-collisional astrophysical plasma (Pistinner & Eichler 1998;Gary & Li 2000;Roberg-Clark et al 2016;Roberg-Clark et al 2018;Komarov et al 2018). The necessity of a heat flux suppression mechanism is suggested by observations of the temperature profile of hot gases in galaxy clusters (e.g., Cowie & McKee 1977;Bertschinger & Meiksin 1986;Zakamska & Narayan 2003;Wagh et al 2014;Fang et al 2018).…”
Section: Introductionmentioning
confidence: 99%